2022
DOI: 10.3389/fpsyg.2022.962830
|View full text |Cite
|
Sign up to set email alerts
|

Counterintuitive consequences of COVID-19 on healthcare workers: A meta-analysis of the relationship between work engagement and job satisfaction

Abstract: BackgroundStudies conducted in the health sector have determined a positive relationship between job satisfaction and work engagement. However, this paper reveals that this relationship turns into a negative or non-significant relationship during the COVID-19 pandemic. We explore the reasons for inconsistency in research findings in this critical period through a meta-analysis.MethodsThis study was conducted according to the PRISMA guidelines and PICO framework. Online databases including Web of Science, Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…In the long run, morally disengaged employees can damage co-workers' productivity, threaten the organization's well-being, lead to the breach of safety behaviors in the workplace, and even cause patient violence (Leidner et al, 2010;Caprara et al, 2014). Since negative behaviors generally undermine the goals and interests of an organization, it is critical to creating an organizational environment that will not allow these behaviors (Yildiz et al, 2022b). Additionally, the responsible and accountable leadership which does not coerce nurses to display CCBs (Podsakoff et al, 1990;Kim, 2014;Purwanto et al, 2021) but empowers and develops the nursing profession with adequate resources, could prove crucial in combatting the precarity experienced during the COVID-19 pandemic by this group of workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the long run, morally disengaged employees can damage co-workers' productivity, threaten the organization's well-being, lead to the breach of safety behaviors in the workplace, and even cause patient violence (Leidner et al, 2010;Caprara et al, 2014). Since negative behaviors generally undermine the goals and interests of an organization, it is critical to creating an organizational environment that will not allow these behaviors (Yildiz et al, 2022b). Additionally, the responsible and accountable leadership which does not coerce nurses to display CCBs (Podsakoff et al, 1990;Kim, 2014;Purwanto et al, 2021) but empowers and develops the nursing profession with adequate resources, could prove crucial in combatting the precarity experienced during the COVID-19 pandemic by this group of workers.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has caused excessive workloads, especially for healthcare professionals, compared to other occupational groups (Cheong et al, 2022). A meta-analytic study conducted on 36 healthcare workers recently found positive relationships (work engagement-job satisfaction) in all studies before COVID-19 turned negative during the COVID-19 process (Yildiz et al, 2022b). Söğütlü et al (2021) also found that COVID-19 has caused an increase in anger, anxiety, insomnia, severity, and emotion regulation difficulty in healthcare workers.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, the involvement of physicians and nurses in healthcare is considered an essential strategy since they are mostly known as frontline health care personnel ( 55 57 ). The engagement of HCWs results in enhancements to HCWs' wellbeing ( 55 ), levels of perceived patient care quality ( 55 ), patient outcomes ( 56 ), data quality ( 53 ), efficiency ( 53 ), innovation ( 53 ), HCWs satisfaction ( 53 , 55 , 58 ), patient satisfaction ( 53 ), performance ( 53 ), and decreased levels of unscheduled time off work ( 55 ). However, research indicates that the nursing voice is often overlooked ( 57 ).…”
Section: Introductionmentioning
confidence: 99%